Peningkatkan Minat Belajar Siswa Berkebutuhan Khusus di SDIT Yaditama Ar-Rahman - Chrisnaji Banindra Yudha; Ilmi Noor Rahmad; Wilda Hilyati; Siti Nur Hasanah (Griya Journal of Mathematics Education and Application, 2023)
This study aims to determine the increase in learning interest of students with special needs in science subjects at SDIT Yaditama Ar-Rahman. The subjects in this study were IV grade students totaling 3 people. This research method is classroom action research which consists of four aspects, namely planning, implementation, observation and reflection. Data collection techniques in this study used observation, interviews and documentation. Based on the results of the study, that in cycle 1 the science learning process was said to be not good, because students with special needs did not appear to have an interest in participating in learning. In addition, the teacher in using the demonstration learning model has not been fully implemented properly in each meeting. Whereas in cycle 2 the interest in learning of students with special needs was quite visible and had increased. Penelitian ini bertujuan untuk mengetahui peningkatan minat belajar siswa berkebutuhan khusus dalam mata pelajaran IPA di SDIT Yaditama Ar-Rahman. Subjek dalam penelitian ini adalah siswa kelas IV berjumlah 3 orang. Metode penelitian ini adalah penelitian tindakan kelas yang terdiri dari empat aspek, yaitu perencanaan, pelaksanaan, pengamatan dan refleksi. Teknik pengumpulan data dalam penelitian ini menggunakan observasi, wawancara dan dokumentasi. Berdasarkan hasil penelitian, bahwa pada siklus 1 proses pembelajaran IPA dikatakan belum baik, karena siswa berkebutuhan khusus belum terlihat memiliki minat dalam mengikuti pembelajaran. Selain itu, guru dalam menggunakan model pembelajaran demonstrasi belum sepenuhnya terlaksana dengan baik dalam setiap pertemuan. Sedangkan pada siklus 2 minat belajar siswa berkebutuhan khsus sudah cukup terlihat dan mengalami peningkatan.